Effect of Onion Peel Tea Supplementation and Exercise Against Hypercholesterolemia and Cardiovascular Risk Factors in Obese Women: Education and Randomized Control Trial - Ahsan, Muhammad; Tasleem, Muhammad Wasim; Rajpoot, Sehrish Rana; Ayub, Hafiz Muhammad; Ahmad, Mehboob; Irshad, Qaisar; Kanwal, Tasleem (Universitas Pendidikan Indonesia (UPI), 2022)
This study aims to evaluate the effectiveness of onion peel tea supplementation on body composition, lipid profile, serum glucose concentration, blood glucose level, hypercholesterolemia-related risk factors, cardiovascular disorders in obese, and overweight females. Females attending Diabetic center National Hospital with a Basal metabolic index greater than 25 are randomly selected, assigned to the control group, aerobic training (AT), Onion Peel tea Supplementation (OPT), as well as AT and OPT groups. OPT group received 33 mg of onion peel tea supplementation after every meal a day in addition to AT for 6 months including 90 min of AT sessions that helped get 80% of the target heart rate. One week before the study and 3 days after the last AT session, all participants were subjected to take their blood samples. In comparison to control group weight, total body fat percentage including visceral fat and subcutaneous fat, body mass index (BMI), high-density lipoproteins (HDL), low-density lipoproteins, blood pressure, heart rate, and triglycerides show a significant decrease in AT and AT+OPT groups. No significant changes were obtained in HDL and waist to hip ratio. AT gave beneficial effects in improving Cardiovascular risk factors, hypertension, and LDL.Â